Management of Tuberculosis: Are the Practices Homogeneous in High-Income Countries? - Frédéric Méchaï; Hugues Cordel; Lorenzo Guglielmetti; Lorenzo Guglielmetti; Alexandra Aubry; Alexandra Aubry; Mateja Jankovic; Miguel Viveiros; Miguel Santin; Delia Goletti; Emmanuelle Cambau; Emmanuelle Cambau (Frontiers Media S.A., 2020)
Objectives: To evaluate and compare practices regarding the diagnosis, isolation measures, and treatment of tuberculosis (TB) in high-income countries and mainly in Europe.Materials and Methods: A survey was conducted from November 2018 to April 2019 within the European Society of Clinical Microbiology and Infectious Diseases Study Group for Mycobacterial Infections (ESGMYC). The practices observed were compared to the main international guidelines.Results: Among 136 ESGMYC members, 64 (17 countries) responded to the questionnaire. In their practice, two (20.7%) or three sputum samples (79.3%) were collected for the diagnosis of pulmonary TB, alternatively induced sputum (n = 37, 67.2%), bronchoscopy (34, 58.6%), and gastric aspirates (15, 25.9%). Nucleic acid amplification tests (NAATs) were performed by 41 (64%) respondents whatever the smear result and by 47 (73%) in case of smear-positive specimens. NAAT and adenosine deaminase measurement were used for extrapulmonary TB diagnosis in 83.6 and 40.4% of cases, respectively. For isolation duration, 21 respondents (42.9%) were keeping isolation until smear negativity. An initial treatment without ethambutol was offered by 14% (n = 9) of respondents. Corticosteroid therapy, cerebrospinal fluid opening pressure testing, and repeated lumbar puncture were carried out for central nervous system TB by 79.6, 51.9, and 46.3% of the respondents, respectively. For patients with human immunodeficiency virus-TB coinfection, the preferred antiretroviral therapy included dolutegravir 50 mg twice a day (56.8%). Comparing with the recommendations of the main guidelines, the practices are not totally consistent.Conclusion: This study shows heterogeneous practices, particularly for diagnosis, and isolation, although rapid molecular testing is implemented in most centers. More standardization might be needed.